FERMENTED GOAT MILK AND STINGLESS BEE HONEY MODULATE INTESTINAL LACTIC ACID BACTERIA AND BODY WEIGHT IN DIABETIC RATS MODEL - Rinita Amelia; Dessy Abdullah; Ira Suryanis; Yudha Endra Pratama; Melya Susanti (Nusantara Hasana Journal, 2026)
Diabetes mellitus is associated with intestinal dysbiosis and body-weight loss. Fermented goat milk provides probiotic lactic acid bacteria (LAB), whereas stingless bee honey contains oligosaccharides with prebiotic potential. This study evaluated their effects on body weight and intestinal LAB in diabetic rats. Streptozotocin-induced diabetic Sprague Dawley rats were assigned to five groups (n = 6): healthy control (K−), diabetic control (K+), fermented goat milk (P1, 1 mL/day), stingless bee honey (P2, 0.4 mL/day), and fermented goat milk supplemented with 5% stingless bee honey (P3, 1 mL/day) for 8 weeks. Body-weight change and intestinal LAB counts were analyzed using one-way ANOVA and Tukey's HSD test. Body-weight change differed significantly among groups (p = 0.0155). P2 showed the greatest weight gain, whereas K+ exhibited the greatest weight loss. Intestinal LAB counts also differed significantly (p < 0.001), with P2 showing the highest LAB population, followed by P1 and P3. Fermented goat milk and stingless bee honey increased intestinal LAB and alleviated diabetes-associated body-weight loss, with stingless bee honey producing the greatest overall effect.